+0  
 
0
60
3
avatar+1164 

Please help, ty!

RainbowPanda  Apr 23, 2018
 #1
avatar+87294 
+2

4x^2 + 4y^2 - 4x + 12y - 6  = 0     add 6 to both sides

 

4x^2  - 4x + 4y^2 + 12y   =  6        complete the square on x and y

 

4(x^2 - x + 1/4)  + 4 (y^2 + 3y + 9/4)   =  6  + 1  + 9

 

4(x - 1/2)^2  +  4(y + 3/2)^2  =  16       divide through by 4

 

(x - 1/2)^2  + ( y + 3/2)^2  =   4   ⇒   "D"

 

 

cool cool cool

CPhill  Apr 23, 2018
 #2
avatar+87294 
+2

center (-2,3)   point  (4, -3)

Since  (4, - 3)  is on the circle, we need to find the distance  between this point and the center....that will be the radius, r...so we have...using the distance formula

 

√ [ (-2-4)^2  + ( -3 - 3)^2  ]  =  √ [ (-6)^2 + (-6)^2]  = √ [36 + 36]  = √72   = r

 

So....the equation is  

 

(x  - h)^2  + (y - k)^2  = r^2      where (h, k)  is the center and  r^2  = 72

 

(  x -  -2)^2 + ( y - 3)^2  = 72

 

(x + 2)^2  + ( y - 3)^2  = 72 ⇒    "A"

 

 

cool cool cool

CPhill  Apr 23, 2018
 #3
avatar+87294 
+2

focus   ( 4, - 3)    directrix   x = -2

Since the directrix lies to the left of the focus, this parabola  opens to the right

The y coordinate of the vertex will  be  -3

The x coordinate will be :  [x coordinate of the focus plus the directrix] / 2  =     [ 4  +  - 2] / 2   =   2/2  = 1

 

We have this form

 

4p ( x - h)  =  (y - k)^2     where  the vertex  is  (h, k)  = ( 1 , -3)

 

And  p  will be the distance between the vertex and the focus  =  3 units....since the parabola opens to  the right, this will be  positive

 

So....putting this all together, we have

 

4(3)(x - 1)  = ( y -  -3)^2

 

12 ( x - 1)  =  ( y + 3)^2

 

(y + 3)^2  = 12 ( x  - 1)   ⇒  "D"

 

 

cool cool cool 

CPhill  Apr 23, 2018

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.